Commodity Transport Studies Tea - Planning Commission (Planning Commission, 1967)
The Chinese had a monopoly of tea trade, which gradually dwindled Against their sports 1896 30G Million lbs . (136 million Kgs.) the exports in 1940 were 30 million lbs, (13.6 million Kgs.) Experiments in cultivation of tea in India were conducted as far back as 1730. In 1834, Lord Ben tick appointed a Committee to go into the question of cultivation of tea in India. The areas recommended were the Himalayan region, eastern frontiers, Nilgais and western ghats of South India.
Joint Technical Group for Transport Planning Planning Commission